2019
DOI: 10.5194/tc-13-735-2019
|View full text |Cite
|
Sign up to set email alerts
|

Role of discrete water recharge from supraglacial drainage systems in modeling patterns of subglacial conduits in Svalbard glaciers

Abstract: Abstract. As the behavior of subglacial water plays a determining role in glacier dynamics, it requires particular attention, especially in the context of climate warming, which is increasing ablation and generating greater amounts of meltwater. On many glaciers, water flowing from the glacier's surface is the main source of supply to the subglacial drainage system. This system is largely influenced by the supraglacial drainage system, which collects meltwater and precipitation and rapidly delivers it to discr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…SAR SI of Hansbreen covered at least 7 km 2 in 2007 and 2010, and since 2012 has not been distinguished as a vast area. This is probably a consequence of negative mass balance, changes in the glacier topography (Błaszczyk et al 2019a) and the effective drainage system of Hansbreen (Decaux et al 2019). Dunse et al (2009) observed an increase in firn area extent of Austfonna between the 2003 and summer surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAR SI of Hansbreen covered at least 7 km 2 in 2007 and 2010, and since 2012 has not been distinguished as a vast area. This is probably a consequence of negative mass balance, changes in the glacier topography (Błaszczyk et al 2019a) and the effective drainage system of Hansbreen (Decaux et al 2019). Dunse et al (2009) observed an increase in firn area extent of Austfonna between the 2003 and summer surface.…”
Section: Discussionmentioning
confidence: 99%
“…Müller 1962;Dyurgerov et al 2009), water drainage (e.g. Jansson et al 2003;Decaux et al 2019), surface energy balance (e.g. Braun and Hock 2004;Hoffman et al 2008) or microbiology of glacier habitats (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these aquifers may promote microbial production (e.g., Anesio et al, 2017), and are the focus of ongoing research on glacier ecology (Hodson et al, 2015). In general, more sophisticated drainage system models have to be developed, to account for differences in spatially distributed or localized recharge (Gulley et al, 2012;Decaux et al, 2019). However, our understanding of processes that control the vertical percolation of surface meltwater and associated firn warming needs to be refined, and studies of horizontal water motion are largely absent.…”
Section: New Challengesmentioning
confidence: 99%
“…Depending on sensor payload, drifters can be used for a wide range of applications, including coastal and ocean surface current monitoring (Boydstun et al, 2015;Jaffe et al, 2017) to estimate river bathymetry and surface velocities (Landon et al, 2014;Almeida et al, 2017) and to collect imagery for underwater photogrammetry (Boydstun et al, 2015). Recent payloads in river studies included sensors for temperature (e.g., Tinka et al, 2013;Oroza et al, 2013;Allegretti, 2014), dissolved oxygen (e.g., D'Este et al, 2012;Tinka et al, 2013), pH (e.g., Tinka et al, 2013;Arai et al, 2014), turbidity (e.g., Marchant et al, 2015), GPS receivers (e.g., Stockdale et al, 2008;Tinka et al, 2013), acoustic Doppler current profilers (e.g., Tinka et al, 2009;Postacchini et al, 2016) and inertial measurement units (e.g., Arai et al, 2014). Additionally, sensor payloads in oceanographic applications included devices for the measurement of conductivity (e.g., Reverdin et al, 2010;Jaffe et al, 2017), chlorophyll (e.g., Jaffe et al, 2017) and underwater imagery (e.g., Boydstun et al, 2015;Xanthidis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%